Ethnic Diversity and Economic Performance - Alesina, Alberto; La Ferrara, Eliana (Journal of Economic Literature, 2005)
We survey and assess the literature on the positive and negative effects of ethnic diversity on economic policies and outcomes. Our focus is on communities of different size and organizational structure, such as countries, cities in developed countries, and villages and groups in developing countries. We also consider the endogenous formation of political jurisdictions and highlight several open issues in need of further research, in particular the endogenous formation of ethnic identity and the measurement of ethnic diversity.